Glucocorticoid and Mineralocorticoid Effects on Adrenocorticotropin and β-Endorphin in the Adrenalectomized Rat - Alan T. Lim; B. A. K. Khalid; Judith Clements; John W. Funder (The Journal of Clinical Investigation, 1982)
Immunoreactive ACTH (ir-ACTH) and immunoreactive β-endorphin (ir-βEP) were determined in plasma, anterior pituitary, neuro-intermediate lobe, and hypothalamus of sham-adrenalectomized rats, and adrenalectomized rats given six daily injections of vehicle (oil), dexamethasone, 9α-fluorocortisol or deoxycorticosterone. 6 d after adrenalectomy, anterior pituitary ir-ACTH and ir-βEP were double, and plasma levels approximately fivefold those in controls. Adrenalectomy did not alter hypothalamic levels of either peptide, or ir-βEP in neuro-intermediate lobe, in which tissue ir-ACTH was below detection limit at routine dilutions. Dexamethasone (0.2-200 μg/d) concurrently suppressed plasma ir-ACTH and ir-βEP, with a near maximal effect at 20 μg, and a half-maximal effect between 2 and 6 μg; similar dose-response characteristics were found for thymolysis. Step-wise increases in anterior pituitary content of both peptides were found, with no change in hypothalamic levels of either peptide, or neuro-intermediate lobe ir-βEP. 9α-fluorocortisol (0.2-200 μg/d) produced plasma, anterior pituitary, and hypothalamic effects equivalent to dexamethasone, but with one-tenth the potency. Unlike dexamethasone, higher doses of 9α-fluorocortisol significantly elevated neuro-intermediate lobe ir-βEP. Deoxycorticosterone (2-2,000 μg/d) produced no significant changes in plasma, anterior pituitary or hypothalamic levels of either peptide; like 9α-fluorocortisol, doses of >60 μg/d significantly elevated neuro-intermediate lobe ir-βEP. Whereas ir-ACTH and ir-βEP synthesis in and release from the anterior pituitary are under complex negative feedback glucocorticoid control, there exists a mineralocorticoid-specific effect on neuro-intermediate lobe content of ir-βEP.